Collapse and Fire Hazards at the Construction Sites and their Economic Impact on the Nation? - Sayah, Elias B.; Ranadive, Dr. M. S. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The Saudi Economy is losing annually Millions of Saudi Currency and that due to ignorance of the safety requirements. Abdullah Mubarak: capital is a coward and accidents are closely linked to the investment movement in the country. Muhammad Abdullah: some construction companies ignore safety requirements with to save money Engineer Ahmad Ghali: A tough control should be done to construction works. Some entrepreneurs have no idea about the conditions of security and safety. Magdy Tawfiq engineer: Safety requirements must be compulsorily applied to all establishments and construction companies and an information centre about all companies, accidents and construction sites Fawzi Al-buheiri Advisor: current laws are sufficient to deter offenders and required to be activated firmly Attainment Written by: Ahmed Abdullatif achieved: providing security and safety for commercial and industrial installations of the most important challenges facing the national economy as not only a victim of accidents and fires which result in heavy material losses, but to the security and safety relationship to attract new investment and create a safe climate for investment... These challenges, which began with the construction boom and the business for years and was one of the most important manifestations of major expansions in construction projects that require necessarily implemented strong security fence and safety. Since the beginning of the year 2003 started increasing incidents of collapses and fires strikingly at the same time, concern over the ability of the national economy in a balance between the desire to grow and expand and provide protection to the cowardly capital in nature and always seeker areas Before this challenge, there was a formal recognition of the seriousness of the phenomenon on the national economy in the new legislation and decisions that will activate the role of the safety devices in economic activities through civil defense and municipal organizations. . Perhaps the most notable official efforts in this domain awareness events advisory offices and construction companies in the new rules for security and safety after the adoption of the new USA code.